Prison reform and torture prevention under ‘compromised circumstances’ - Jefferson, Andrew M. (Criminology & criminal justice, 2024)
In this article, drawing on two decades studying prisons and prison reform practices in (mostly) southern countries undergoing transition, I examine the challenges facing anti-torture professionals and prison reformers working in the global south and critically interrogate the assumptions of dominant models of reform. Rights and health-based entry points to the prevention of torture and inhumane treatment and prison reform are argued to be necessary but insufficient. I propose the concept ‘compromised circumstances’ to counter the structural biases that diminish and erase ordinary everyday experience. The ‘compromised circumstances’ of countries torn by conflict, inequality, poverty and mundane violence call for innovative interventions based on reflexive social scientific description and analysis. The inevitable sense of dizziness and uncertainty such circumstances induce must be embraced not denied. A dynamic, organic and relational entry point to reform is required.